MODERN DIAGNOSIS METHODS OF IRRITABLE BOWEL SYNDROME IN CHILDREN - Rasulova Saodat Khalimovna (Web of Journals Publishing, 2025)
This article analyzes modern methods of diagnosis of irritable bowel syndrome (IBS) in children. Based on the obtained results, ways of early detection and effective diagnosis of IBS were considered. Modern clinical, laboratory and instrumental diagnostic methods were studied.
Keywords: IBS, pediatric gastroenterology, ultrasound diagnosis, modern methods, intestinal microbiota.